2009
DOI: 10.1021/jp900933c
|View full text |Cite
|
Sign up to set email alerts
|

Rotating Disk Electrode (RDE) Investigation of BH4 and BH3OH Electro-oxidation at Pt and Au: Implications for BH4 Fuel Cells

Abstract: We present a thorough electrochemical study of the mechanism of borohydride oxidation on gold and platinum surfaces via cyclic voltammetry and rotating disk and ring-disk electrode voltammetry. We have paid particularly close attention to the number of electrons transferred (from a theoretical maximum of 8e -), values of the heterogeneous charge transfer rate constant (k b ), the presence of coupled chemical reactions, and adsorbed intermediates. We find that the nature of the electrode (Pt, Au) plays an impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
168
5
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(192 citation statements)
references
References 58 publications
(348 reference statements)
17
168
5
2
Order By: Relevance
“…The oxidation of AB commences at -1.02 V which is 0.08 V more positive than that at a Au microdisc. 15 In the forward sweep an oxidation peak a1 was recorded at -0.84 V followed by a broad oxidation wave a2 from -0.49 to -0.10 V. The location of the anodic features a1 and a2 agree with those reported in our microdisc studies of AB and DMAB oxidation at Au 15,21 and with those reported by Finkelstein et al 25 They identified two regions of mass transport limited current for BH 3 17 for the oxidation of 20 mM AB in 2 M NaOH at 100 mV s -1 at a Au disc. They assigned this to electrooxidation of H 2 generated from the hydrolysis of AB which they confirmed by its disappearance upon the addition of thiourea which inhibits the recombination of surface hydrogen radicals.…”
Section: Electrooxidation Of Ab At Au Discsupporting
confidence: 91%
“…The oxidation of AB commences at -1.02 V which is 0.08 V more positive than that at a Au microdisc. 15 In the forward sweep an oxidation peak a1 was recorded at -0.84 V followed by a broad oxidation wave a2 from -0.49 to -0.10 V. The location of the anodic features a1 and a2 agree with those reported in our microdisc studies of AB and DMAB oxidation at Au 15,21 and with those reported by Finkelstein et al 25 They identified two regions of mass transport limited current for BH 3 17 for the oxidation of 20 mM AB in 2 M NaOH at 100 mV s -1 at a Au disc. They assigned this to electrooxidation of H 2 generated from the hydrolysis of AB which they confirmed by its disappearance upon the addition of thiourea which inhibits the recombination of surface hydrogen radicals.…”
Section: Electrooxidation Of Ab At Au Discsupporting
confidence: 91%
“…It is well known that the nature of the electrode (Pt or Au) plays an important role in the processes involved in BOR in aqueous media (e.g., the presence of coupled chemical reactions and adsorbed intermediates), directly affecting parameters like the number of transferred electrons or the heterogeneous charge transfer rate constant. 22 However, present n values show a behavior which is different from that normally observed in aqueous media and may be attributed to the faster kinetics of BOR at Pt electrodes. 23 In fact, Au electrodes are known to have sluggish BOR kinetics, causing the Au onset potential for BOR to be shifted to the right (more positive potentials) compared to Pt onset potentials.…”
Section: Resultscontrasting
confidence: 59%
“…And despite Au is known for being less active than Pt for borohydride hydrolysis, 10 which generally leads to higher n values for BOR in aqueous media, Finkelstein et al have reported that Pt significantly outperforms Au for BH 4 − oxidation in direct borohydride fuel cells, providing similar electron recovery at much lower anode potentials. 22 For the present case, as DMSO does not contain any protic H source, borohydride hydrolysis should not be promoted by the solvent, allowing Pt to exhibit higher coulombic efficiencies (i.e., higher n) than Au. On the other hand, it must be considered that although molecular sieves were used to dry the DMSO solvent, there is likely some minor water content in solution, due to the highly hygroscopic nature of DMSO.…”
Section: Resultsmentioning
confidence: 95%
“…Although the theoretic BOR potential is −0.41 V vs. RHE (at pH 14) anode − oxidation is reported to be more negative than direct BH 4 − oxidation and hydrogen evolution. 10,22 In contradiction to this, Dong et al attributed the negative onset potential to direct oxidation of BH 4 − . 23 Further mechanistic aspects and details are not discussed at this point.…”
Section: Resultsmentioning
confidence: 97%